POLICY IN THE FIELD OF HEALTH: NATIONAL ISSUES AND GLOBAL CHALLENGES - Кириленко, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Content analysis, strategies and trends of contemporary policy in maintaining the health of the population at the national and global levels. The main problems of public administration development of health care in Ukraine in conditions of liberalization and globalization.